Physical and physiological response to different modes of repeated sprint exercises in basketball players - Paulauskas, R.; Kamarauskas, P.; Nekriodius, R.; Bigwood, N. M. (Journal of Human Kinetics, 2020)
The aim of this study was to investigate changes in physical and physiological responses to different modes of repeated sprint exercise by measuring speed, total time (sum of sprints), fatigue index, heart rate, local oxygen saturation, total haemoglobin content, and blood lactate. The volume of the physical load (distance, work and rest ratio) was the same in both exercises, but load specifics were different. The first mode consisted of 10 x 30 m sprints (with one change of direction) interspersed with 30 s of passive recovery, while the second mode of 20 x 15 m shuttle sprints interspersed with 15 s of passive recovery. Both exercise modalities were repeated three times with a five-minute rest interval between bouts with 7 days of recovery between each testing condition. Twelve highly trained male basketball players volunteered to participate in this study. Our study showed that different modes of repeated sprint exercises elicited a different physical response and metabolic demand. Longer sprints with directional changes placed a higher demand on the anaerobic glycolytic system compared to straight and more frequent sprint exercises. However, players` fatigue was more noticeable in shorter and more frequent sprints. Heart rate responses and local use of O2 showed a similar activity of aerobic reactions through the different exercises. During the sprints, players` SmO2 fell to 40% and recovered to the level of about 80% during passive rest intervals without showing differences in both modalities. This suggests that both types of sprint exercises can similarly stimulate aerobic metabolism.